My name is not Alexander - Fosberry, Jennifer (Sourcebooks Jabberwocky, 2011)
Through his imaginative journey, Alexander discovers how great men become heroes: a tough president has a soft spot for nature, a proud warrior is also the most peaceful, and sometimes, being brave about what makes you different will not only help you break records, but inspire others.